Capacitive storage at nitrogen doped amorphous carbon electrodes: structural and chemical effects of nitrogen incorporation - Colavita, Paula; Hoque, Md. Khairul; Behan, James A.; Stamatin, Serban N.; Zen, Federico; Perova, Tatiana S. (My University, 2019)
Nitrogen incorporated carbon materials play an important role in electrochemical energy conversion technologies from fuel cells to capacitive storage devices. This work investigates the effects of nitrogen incorporation on capacitance, work function and semiconductor properties of amorphous carbon thin film electrodes. Nitrogenated electrodes (a-C:N) electrodes were synthesized via magnetron sputtering and characterized using X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy (UPS), Raman spectroscopy, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). EIS was carried in both aqueous (0.1 M KCl) and organic (0.1 M TBAPF6/acetonitrile) electrolytes to discriminate between pseudocapacitive contributions and changes to semiconductor properties of the materials arising from structural and chemical disruption of the graphitic carbon scaffold. Raman and UPS spectroscopy both suggest that nitrogen incorporation increases the metallic character of the disordered carbon matrix at low-intermediate concentrations, whereas further nitrogen incorporation results in significantly more defective carbon with small graphitic cluster size. EIS studies in 0.1 M KCl indicate that the capacitance of a-C:N electrodes increases relative to nitrogen-free a-C electrodes due to a combination of microroughness and pseudocapacitive contributions in parallel to those of the double layer capacitance. Results in 0.1 M TBAPF6 in acetonitrile which are dominated by the interfacial capacitance, show that initial nitrogen incorporation into the disordered carbon scaffold compensates for p-type properties in the disordered carbon matrix, resulting in an increase in metallic character. Greater levels of nitrogenation, are instead disruptive and increase defect density while decreasing the double layer capacitance.
PUBLISHED
Keywords: Nitrogen; Carbon electrodes